The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1021/la0205654
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Mediated Stepwise Assembly of Three-Dimensional Organized Multiporphyrin Arrays Directly on Solid Substrates

Abstract: A palladium-mediated assembling strategy was developed to construct organized, three-dimensional multiporphyrin arrays, wherein layers of multiporphyrin arrays can be embedded via a Py-Pd-Py coordination unit directly on solid substrates. Multilayers of the multiporphyrin arrays were characterized by use of X-ray photoelectron, UV-vis, and fluorescence spectroscopy. A linear increase was observed for the absorption intensity of the Soret band of porphyrins or the π-π* charge transition with the layer numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 40 publications
2
47
2
Order By: Relevance
“…These curves revealed a broad absorption band between 200 and 500 nm, which could be attributed to the π−π* and n−π* electron transfer of the Pd− Py coordination unit, H 2 ase and MWNTs. 39 The absorption intensity at 290 nm was proportional with the layer numbers assembled (see the graph inserted in Figure 5), which indicated that similar amounts of the nanolinkers and Na 2 PdCl 4 connectors were assembled for each bilayer. A close inspection of the absorption increase could find a relatively larger increase for the coordination of the PdCl 4 2− ions, together with a smaller one for the coordination or adsorption of the bionanocomposites.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These curves revealed a broad absorption band between 200 and 500 nm, which could be attributed to the π−π* and n−π* electron transfer of the Pd− Py coordination unit, H 2 ase and MWNTs. 39 The absorption intensity at 290 nm was proportional with the layer numbers assembled (see the graph inserted in Figure 5), which indicated that similar amounts of the nanolinkers and Na 2 PdCl 4 connectors were assembled for each bilayer. A close inspection of the absorption increase could find a relatively larger increase for the coordination of the PdCl 4 2− ions, together with a smaller one for the coordination or adsorption of the bionanocomposites.…”
Section: ■ Results and Discussionmentioning
confidence: 88%
“…A possible reason may be that the PdCl 4 2− ions could coordinate with pyridine substituents more efficiently than those reported previously at the interfaces. 39 The assembling process was monitored by measuring the absorption spectra, XPS, FE-SEM, and AFM images as described below. Figure 5 shows the absorption spectra for the (Pd/MWNTPVPMe@H 2 ase) n LBL multilayers on the quartz surface after each assembly of the connector of Na 2 PdCl 4 and the nanolinker of MWNT-PVPMe@H 2 ase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Other nanoscaled materials of porphyrins, such as tubes, rods, and crystals, can be formed from simple commercially available compounds or from more complex molecular designs. [18, 87] Self-assembled porphyrinic materials generally require specifically designed recognition motifs in predefined geometries to affect specific architectures. Conversely, the construction of self-organized materials, such as ONPs, does not require complex exocyclic moieties.…”
Section: Discussionmentioning
confidence: 99%
“…174 Imahori and coworkers employed a supramolecular approach to organize porphyrin-fullerene doublecable structures (Scheme 65). 183 Alternating deposition of pyridylporphyrin 137 and K 2 PdCl 4 through pyridyl-to-Pd coordination, the method originally developed by Qian et al, 184 followed by incorporation of fullerene 138 through pyridylto-zinc coordination gave a surface-oriented double-cable structure on the SnO 2 electrode, that exhibited enhanced photobipolar properties. Employing specific interactions of proteins, straightforward supramolecular assemblies were obtained.…”
Section: A Supramolecular Organization On An Electrode Surfacementioning
confidence: 99%